The Role of Takmir in Mosque Fund Management on Increasing Trust Community for Zakah, Infaq and Alms (Study on the Great Mosque of Pelita Samarinda) - Isna Yuningsih; Andi Martina Kamaruddin; Adi Tri Pramono (AFEBI Islamic Finance and Economic Review, 2020)
This study aims to determine the role of takmir in managing mosque funds so that they can increase and maintain public trust in zakah, infaq, and alms at the Great Mosque of Pelita Samarinda. The methodology used in this study is qualitative with a descriptive approach. The informants in this study were the administrators of the Great Mosque of Pelita Samarinda which included the Mosque Secretary, the Treasurer of the Mosque, and the Chair of the Education Section/Taklim Assembly of the Great Mosque of Pelita Samarinda, as well as the congregation of the Great Mosque of Pelita Samarinda. Data collection techniques used are interviews, library sources, and documentation. The results of this study indicate that the role of takmir is very vital in increasing public trust in zakah, infaq, and alms at the Great Mosque of Pelita Samarinda. The contributions of this research include being able to improve the quality and responsibility of the mosque takmir in terms of being accountable for the trust of the congregation, by providing evidence of transparent income and expenditure reports.Keywords: Great Mosque of Pelita Samarinda; Takmir Mosque; Fund Management